Sufisme Perkotaan dan Nalar Beragama Inklusif - Rosidin Rosidin (Balai Penelitian dan Pengembangan Agama Semarang, 2014)
AbstractSocial conflicts rises frequently because of religious crisis that preceded religious truth claims over the interpretation and strength of religious exclusiveness. This spiritual crisis made uneasy by religious leaders that led to the various assemblies of dhikr or city Sufism, one panel of Jamaat Muji Prophet (Jamuro). This descriptive qualitative study was conducted using deep interviews, relevant documentations and observation This research aimed to determine (1) how the background standing, (2) public response and (3) the role played by the Assembly Jamaat Muji Prophet (Jamuro) in deradicalization efforts of religious movements. This research used qualitative as well as descriptive approaches. Data was obtained by deep interview, observation, and relevant documentations. The results of this study are: first, Jamuro founded in 2004 in Surakarta by Islamic theologians, kyai, habib, and Islamic figures from Nahdliyin to preserve the tradition of clerical predecessors in preaching . This movement aimed to continue Islamic propaganda tradition by earlier ulamas. The diversity of the radical movement in Surakarta contributed to the birth of Jamuro in hopes of reviving spirituality in town disappearing and the number of radical Islamic movements. (2) Most of communities accepted Majlis Jamuro, so that it derived others, like Jimat (Jamaah Iman Manteb Ati Tentrem) and Tomat (Tobat Maksiat). Expanding its range not only in the former residency of Surakarta and its surroundings, even Semarang. (3) Jamuro in the context of de-radicalization seen in its efforts to fortify themselves from the many familiar and radical Islamic movements through Tausyiah which will hopefully prevent jama’ahnya to commit violence in the name of religion.Keywords: Urban Sufism, Religious Movements, Deradicalization, Majlis Jamuro. AbstrakKonflik sosial seringkali muncul karena krisis keagamaan yang diawali klaim kebenaran atas tafsir dan kuatnya sikap eksklusif dalam beragama. Krisis spiritual ini membuat gelisah para tokoh agamasehingga memunculkan berbagai majelis dzikir atau sufisme kota, salah satunya majelis Jamaah Muji Rosul (Jamuro). Penelitian kualitatif deskriptif ini dilakukan dengan metode wawancara,dokumentasi dan observasi. Penelitian ini bertujuan untuk mengetahui (1) bagaimana latar belakang berdiri, (2) respon masyarakat dan (3) peran yang dimainkan Majelis Jamaah Muji Rosul (Jamuro)dalam upaya deradikalisasi gerakan keagamaan. Hasil penelitian ini adalah: pertama, Jamuro didirikan tahun 2004 di Surakarta oleh para ulama, kyai, habaib, dan tokoh agama dari kalanganNahdliyin sebagai wadah umat Islam Surakarta untuk melestarikan tradisi ulama pendahulu dalam dakwahnya. Beragamnya gerakan radikal di Surakarta ikut mendorong lahirnya Jamuro denganharapan dapat membangkitkan kembali spiritualitas di kota yang makin pudar serta banyaknya gerakan Islam radikal. Kedua, masyarakat dari berbagai kalangan menyambut baik adanya Jamuro,yang memunculkan rintisan majelis Jamuro kecil, seperti Jimat (Jamaah Iman Manteb Ati Tentrem), dan Tomat (Tobat Maksiat). Persebarannya makin meluas tidak hanya di eks karesidenan Surakarta dan sekitarnya, bahkan Semarang. Ketiga, Jamuro dalam konteks deradikalisasi terlihat dalam upayanya membentengi diri dari banyaknya paham serta gerakan Islam radikal melalui tausyiahyang diharapkan akan mencegah jama’ahnya untuk melakukan kekerasan yang mengatasnamakan agama.Kata kunci: Sufisme kota, gerakan keagamaan, deradikalisasi, Majlis Jamuro.